ENVIRONMENTAL RISKS IN A SERVICE FOR SECONDARY CARE FOR HEALTH - Juliana Trebi Penatti; Tatiane Bonametti Veiga; Adriana Aparecida Mendes; Ana Paula Milla dos Santos; Angela Maria Magosso Takayanagui (Universidade Federal do Paraná, 2013)
This research was undertaken with the objective of identifying and quantifying the environmental risks in a service for secondary care for health, taking into account the level of schooling of, and the activities carried out by, the participants of the study, who made up the multidisciplinary team, with a view to contributing to the achieving of better occupational health conditions. This is descriptive and exploratory research, with a quali-quantitative approach. Based on the participants' professional profiles and functions, it was possible to identify the knowledge and perceptions that these have on the risks, as well as identifying and quantifying them. The results evidence concern about questions relevant to working conditions and to the environmental risks present in their daily activities, and allow one to generate new approaches to the managerial work, principally of an educational and structural character in the work